Code-switching in the TEFL Undergraduate Classroom - Al Chal, Sandra (2022)
Code-switching is the usage of two or more languages when speaking and it happens mostly in communities that are bilingual. This paper is an exploratory qualitative study which focuses on code-switching in TEFL undergraduate courses at a private university in Lebanon. The aim of this study was to discover teachers’ perceptions and practices regarding code-switching in first and second year TEFL major classrooms at a university in Lebanon. It also investigated students’ perceptions regarding code-switching in the first-year undergraduate TEFL major in the university. The study attempted to see whether teachers and students perceive code-switching as a beneficial tool in the classroom or not. The four instructors of the first and second year TEFL undergraduate courses were interviewed using in-depth interviews. Their classrooms were observed three times using non-participant observations. The students were also interviewed using focus-group interviews. The findings of this study supported the view that code-switching in the language classroom is a facilitating tool for the students. The findings also showed that switching to the native language should be allowed only in certain situations when it is needed and that it has many benefits for the students, as supported by previous findings. However, further research should be conducted in more than one campus of a university and with larger number of participants in order to get a wider view of the Lebanese context. In addition, longitudinal studies should be conducted to see the difference between the levels of code-switching at the beginning of the semester and at the end of it.